2001
DOI: 10.1046/j.1528-1157.2001.4220256.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Valproate to Subdural Cerebrospinal Fluid, Subcutaneous Extracellular Fluid, and Plasma in Humans: A Microdialysis Study

Abstract: Summary We sought to study the time course of the distribution of valproate (VPA) to subdural cerebrospinal fluid (CSF) in relation to subcutaneous extracellular fluid (ECF) and plasma after a single oral dose and to study the distribution to these three compartments under steady‐state conditions. Microdialysis was used to estimate unbound VPA concentrations in subdural CSF and subcutaneous ECF, and blood samples were drawn for estimation of total and unbound VPA plasma concentrations in four patients with dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…For the estimation of carbamazepine and phenobarbital in subdural cerebrospinal fluid, subcutaneous extracellular fluid and plasma, two patients with drug resistent partial epilepsy, undergoing presurgical evaluation with subdural EEG monitoring, were investigated. Both were part of a previously published study of distribution of valproate to subdural cerebrospinal fluid, subcutaneous extracellular fluid and plasma (Lindberger et al 2001). The patient demographics and drug treatments are shown in table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the estimation of carbamazepine and phenobarbital in subdural cerebrospinal fluid, subcutaneous extracellular fluid and plasma, two patients with drug resistent partial epilepsy, undergoing presurgical evaluation with subdural EEG monitoring, were investigated. Both were part of a previously published study of distribution of valproate to subdural cerebrospinal fluid, subcutaneous extracellular fluid and plasma (Lindberger et al 2001). The patient demographics and drug treatments are shown in table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it can be used to sample subcutaneous extracellular valproate, giving reliable estimates of the protein unbound concentrations in plasma (Lindberger et al 1998). We also used microdialysis to sample cerebrospinal fluid and found that protein unbound subdural cerebrospinal fluid levels of valproate were only slightly lower than unbound levels in subcutaneous extracellular fluid and plasma (Lindberger et al 2001).…”
mentioning
confidence: 99%
“…A microdialysis study in humans demonstrated the pharmacokinetic rationale for acute treatment with VPA. It is based on the rapid distribution of VPA to the brain (75). Recently, Marson et al (83) performed a meta-analysis that compares VPA with carbamazepine in the monotherapy of epilepsy.…”
Section: Epilepsymentioning
confidence: 99%
“…It has an advantage over other sampling techniques in that it can be used to follow temporal variations in the generation and release of a substance at a discreet location within the tissue space. Since its initial use in the brain of experimental animals for the recovery of neurotransmitters and other small hydrophilic solutes, 1 microdialysis has been adapted for use in many other tissues, including skin, 2-9 adipose tissue, 10 muscle, 11 , 12 and gastrointestinal tract. 13 However, the ability to recover molecules of higher molecular mass has, until recently, been limited by the availability of dialysis probes with high molecular weight cutoffs (MWCOs).…”
Section: Introductionmentioning
confidence: 99%